Scientific prowess - Abd Razak, Dzulkifli (2003)
The future of our homeland must necessarily be a future of men of sciences. THIS quotation was often heard during our visit to Cuba especially from almost all the researchers we met. Fidel Castro said it more than 40 years ago in I960, a year after the fall of the former regime. It is the vision of the person who has been leading Cuba since. This grand mission is now unfolding in full view of the scientific world. Its success is recognised by the World Health Organization (WHO) and many other institutions of international standing. In fact, in the early 1980s, Cuba articulated its goal to become one of the world's leading countries in the field of medicine. Between 1970 and 1979, "green" medicine was introduced, that is, the use of herbs and plants in the treatment of a variety of diseases. The application of acupuncture was also started.